Compressive behaviour of thin-walled square tubular columns filled with high-strength steel section and precast compound concrete segments. (June 2020) - Wu, Bo; Lin, Lang; Zhao, Junxian; Shen, Chao
Abstract: Different from small-scale recycled aggregates (≤31.5 mm) in recycled aggregate concrete, recycling waste concrete in structural members in the form of compound concrete, constructed with large-scale (60–200 mm) demolished concrete lumps (DCLs) and fresh concrete, provides a viable option to designers. Such DCLs can be mixed with fresh concrete in shop to produce precast concrete segments (PS-DCLs), which can be transported to construction site to expedite construction process of the structural members with the PS-DCLs. In this paper, an innovative thin-walled square tubular column filled with I-shaped high-strength steel (HSS) section and PS-DCLs is proposed to enable easy application of the DCLs into vertical structural members and address the shortcomings of the HSS section. The PS-DCLs are placed into the gap between the outer tube and the inner HSS section, using in-filled grout as bonding among them, to produce composite column. A new precasting procedure for fabricating such columns is proposed. Axial compression tests were conducted to investigate the effects of fabrication procedure, yield strength of the inner steel section, replacement ratio of the DCLs, and configuration of the PS-DCLs on the compressive behaviour of the proposed columns. The test results show that the precast columns constructed using the proposed procedure had axial compression capacities comparable to those cast in place. A practical method for predicting the load-bearing capacity of such columns is proposed and validated against the experiments and published data from previous studies. It shows better agreement with the experimental data than the existing approaches. An effective strength index is proposed for utilizing the strength contribution of steel section in the proposed columns, and recommendations for practical selection of appropriate materials for the steel section are presented. Highlights: An innovative thin-walled square tubular column filled with HSS section and precast compound concrete segments is proposed. The precast segments contain demolished concrete lumps (PS-DCLs) that enable easy application of DCLs into vertical members. Tests were conducted on 15 specimens to examine the axial compressive behaviour of such columns. The precast columns show comparable axial compression capacities to the cast-in-place specimens. An approach considering confinement from tube and HSS section is proposed to predict compression capacity of such column.